2010
DOI: 10.1177/0009922810363155
|View full text |Cite
|
Sign up to set email alerts
|

Association of Anxiety and Depressive Symptoms and Adiposity Among Adolescent Females, Using Dual Energy X-ray Absorptiometry

Abstract: The purpose of this study is to evaluate the association between anxiety and depressive symptoms and obesity among adolescent females using objective measures of adiposity, and evaluate for moderating effects of race and age. This is a cross-sectional analysis of 198 females ages 11, 13, 15, and 17 years (mean 14.6, SD 2.2). Adiposity measures include BMI, BMI Z-score (BMI-Z), percent body fat from Dual Energy X-ray Absorptiometry (DXA), and fat distribution (fat mass upper vs. lower body regions from DXA). Sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 30 publications
2
39
0
3
Order By: Relevance
“…Consistent with adult studies, children with more depressive symptoms are at increased risk of being obese (Cortese et al, 2009;Goodman and Whitaker, 2002;Hillman et al, 2010;Mustillo et al, 2003;Richardson et al, 2006). Few childhood studies, however, have examined the influence of depressive symptoms on CVD risk factors other than obesity.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Consistent with adult studies, children with more depressive symptoms are at increased risk of being obese (Cortese et al, 2009;Goodman and Whitaker, 2002;Hillman et al, 2010;Mustillo et al, 2003;Richardson et al, 2006). Few childhood studies, however, have examined the influence of depressive symptoms on CVD risk factors other than obesity.…”
Section: Introductionmentioning
confidence: 73%
“…Two other studies have also reported associations between depressive symptoms and adiposity only in girls (Chaiton et al, 2009;Hillman et al, 2010). A possible mechanism underlying the gender differences between anxious-depressive scores and adiposity at age 14 may be sex-related differences in hormones such as leptin.…”
Section: Discussionmentioning
confidence: 92%
“…In Nigeria, the burden of overweight and obesity is increasing and estimation showed over 20 percent increase in the burden within the last fifteen years (Akarolo-Anthony et al, 2014;Adebayo et al, 2014;Chukwuonye et al, 2013;Wahab et al, 2011). Obesity impairs mental health (Hillman et al, 2010) which could affect productivity, places large burden on health system and leads to fall in productivity following absenteeism, decreased productivity of employees while at work, disability, and premature mortality (Hammond and Levine, 2010;Ricci and Chee, 2005;Fontaine et al, 2010). World Health Organization Global Comparative Estimate showed higher prevalence of overweight and obesity in women than men (Ono et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…[45][46][47] Genç erişkinlerde yapılan çalışmalarda, anksiyete ve depresyon semptomlarının BKİ ile pozitif yönde ilişkili olduğu görülmüştür. 45,46 Ancak, Hillman ve ark.nın çalışmasında, adolesan döne-mindeki kızlarda BKİ'nin bu semptomlar üzerinde etkisi olmadığı belirtilmiştir.…”
Section: Discussionunclassified
“…45,46 Ancak, Hillman ve ark.nın çalışmasında, adolesan döne-mindeki kızlarda BKİ'nin bu semptomlar üzerinde etkisi olmadığı belirtilmiştir. 47 Çalışmalarda destekleyici faktörlere BKİ'nin etkisi araştırılsa da Morrison ve ark., vücut yağ oranının depresyon semptomları için en tutarlı ön gösterge olduğunu rapor etmişlerdir. 48 BKİ, toplam yağdaki minimal artışı göstermediği için vücut yağ oranı, adipozitenin daha objektif ve fizyolojik bir ölçümüdür.…”
Section: Discussionunclassified